John Dewey's Constructivist Learning Theory and Its Implementation in Islamic Religious Education Learning - Hermanto, Mohammad; Jayana, Thoriq Aziz (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2023)
This article first studies the constructivist learning theory from John Dewey's point of view, and then it investigates the extent to which the theory can be applied to PAI learning. In order to develop a well-established theory that is connected to constructivism, the process that is utilized is a literature review. The results of this research led the researchers to the conclusion that the constructivism learning theory has the capacity to engage students in active learning, even if they are required to construct their own understanding. This, in turn, makes the knowledge more relevant for the students receiving it.